PENONJOLAN PERAN SEMANTIS DAN KONSTRUKSI GRAMATIKAL PASANGAN VERBA -I DAN -KAN: KAJIAN GRAMATIKA KONSTRUKSIONAL BERBASIS KORPUS ATAS MENAWARI/MENAWARKAN - Gede Primahadi Wijaya Rajeg (Masyarakat Linguistik Indonesia, 2023)
This paper presents quantitative corpus analyses of the profiled participant/semantic roles and the preferred grammatical constructions of semantically similar Indonesian verb-pair suffixed with -i and -kan. Menawari/menawarkan ‘to offer’ pair is chosen as a case study. Couched within the Construction Grammar and Frame Semantics theories, the analyses revealed that each verb differs regarding the profiled semantic roles within the preferred grammatical constructions the verb occurs in. Menawari strongly profiles Offerer, Potential_recipient and Theme in Double-Object Construction, while menawarkan only profiles Offerer and Theme in Monotransitive Construction. Although the quantitative findings confirm the theoretical hypothesis of the constructional behaviours for menawari/menawarkan, the study also discovers previously unpredicted constructional variation for menawari. Such variation (i) has a typological implication concerning the grammatical alignments of trivalent verbs and (ii) raises an intriguing question regarding constructional contamination by the constructional profile of the more frequent form (i.e., menawarkan) that is paradigmatically related to menawari.